The Role of Brand Personality in Social Media on Brand Loyalty in the Case of Gojek - Clarissa Laurella; Kenly Salim (iBuss Management, 2021)
As the usage of the Internet continues to grow, new business opportunities arise rapidly. The number of online service companies snowballs at an unprecedented rate. An excellent example is Gojek, an Indonesian decacorn multi-service platform and digital payment company. As an effort to support its outstanding performance, Gojek utilizes social media to communicate and relay its messages to consumers. The researchers are intrigued by the way social media assisted the success of Gojek and how it can be further explored to support Gojek’s performance and other companies. This research ascertains the role of brand personality in social media on brand loyalty with brand satisfaction as a mediating variable, in the case of Gojek. Data were collected through an online questionnaire with 170 respondents who have used Gojek and have lived in Indonesia for the past six months. Results were processed using the PLS-SEM method. Findings show that brand personality significantly affects brand loyalty. Also, brand satisfaction partly mediates the relationship between brand personality and brand loyalty.Keywords:Brand Personality, Brand Satisfaction, Brand Loyalty, Social Media, Gojek.